Global Factors in the Term Structure of Interest Rates - Abbritti, Mirko (IMF Working Papers; Working Paper, 2013)
This paper introduces global factors within a FAVAR framework in an empirical affine term structure model. We apply our method to a panel of international yield curves and show that global factors account for more than 80 percent of term premia in advanced economies. In particular they tend to explain long-term dynamics in yield curves, as opposed to domestic factors which are instead more relevant to short-run movements. We uncover the key role for global curvature in shaping term premia dynamics. We show that this novel factor precedes global economic and financial instability. In particular, it coincides with immediate expectations of permanent expansionary monetary policy during the recent crisis.